Post-operative change in lower limb length in inverted V-shaped high tibial osteotomy with a large correction angle is larger than that with a small correction angle - Seiju Hayashi; Kei Kato; Satoshi Miyazaki; Kazuki Yunokawa (Journal of Joint Surgery and Research)
Purpose: Although inverted V-shaped high tibial osteotomy (iVHTO) is a good option for severe varus deformity requiring a valgus correction angle >15°, it is still unclear whether its several clinical advantages can be applied to varus deformities requiring a valgus correction angle ≤15°. Moreover, no previous studies have revealed why the application of iVHTO was limited to a correction angle >15°. This study aimed to compare post-operative anatomical changes and to determine any applicability of iVHTO for a valgus correction angle ≤15° using three-dimensional (3D) bone models. Methods: Differences in post-operative anatomical alignment changes between iVHTO with >15° of correction (L-iVHTO group) and iVHTO with ≤15° of correction (S-iVHTO group) were examined. A total of 37 knees (18 ​L-iVHTO and 19 ​S-iVHTO) in 27 patients were enrolled. Pre- and post-operative 3D computed tomography bone models were reconstructed using a ZedHTO system. Post-operative anatomical changes (Δ) in posterior tibial slope (PTS), medial proximal tibial angle (MPTA), knee rotation angle (KRA), tibial torsion angle (TTA), patella tilting angle (PTA), Caton–Deschamps index (CDI), tibia length (TL), and lower leg length (LLL) were compared. Results: ΔLLL in the L-iVHTO group (1.8 ​± ​5.6 ​mm) was significantly larger than that in the S-iVHTO group (−1.7 ​± ​4.8 ​mm; p ​< ​0.01). No significant differences were observed among the groups in ΔMPTA, ΔPTS at the medial and lateral tibial plateau, ΔKRA, ΔTTA, ΔPTA, ΔCDI, and ΔTL. Conclusions: Since the characteristics of hemi-open-wedge HTO (OWHTO) and hemi-closed-wedge HTO (CWHTO) might be expressed in iVHTO depending on the correction angle, surgeons should be aware pre-operatively that L-iVHTO will lengthen the LLL and S-iVHTO will shorten the LLL post-operatively.